THE EQUATIONS 3<i>x</i><sup>2</sup>−2 = <i>y</i><sup>2</sup> AND 8<i>x</i><sup>2</sup>−7 = <i>z</i><sup>2</sup>

Type: Article

Publication Date: 1969-01-01

Citations: 363

DOI: https://doi.org/10.1093/qmath/20.1.129

Locations

  • The Quarterly Journal of Mathematics - View - PDF

Similar Works

Action Title Year Authors
+ On the Equation <i>a</i>(<i>a</i> + <i>d</i>)(<i>a</i> + 2<i>d</i>)(<i>a</i> + 3<i>d</i>) = <i>x</i><sup>2</sup> 2000 Tamás Erdélyi
+ Some Properties of the Equation <i>x</i> <sup>2</sup> = 5 <i>y</i> <sup>2</sup> − 4 2016 Serge Perrine
+ The Solutions of <i>x</i><sup><i>y</i></sup> = <i>y</i><sup><i>x</i></sup>, <i>x</i>&gt;0, <i>y</i>&gt;0, <i>x</i>≠<i>y</i>, and their Graphical Representation 1931 H. L. Slobin
+ Certain Recursion Formulas Connected with the Solution of <i>X</i><sup>2</sup> + <i>Y</i><sup>2</sup> = <i>Z</i><sup>2</sup> 1925 P. H. Daus
+ The equation <i>c</i><sub>1</sub><i>x</i><sup>k</sup><sub>1</sub> + … + <i>c</i><sub>s</sub><i>x</i><sup>k</sup><sub>s</sub> = 0 2005 T. D. Browning
+ Minimum Solutions to <i>x</i> <sup>2</sup> − <i>Dy</i> <sup>2</sup> = ± 1 1975 Gregory Wulczyn
+ A Note on the Equation <i>n</i><sup>2</sup>+<i>n</i>+1=<i>p<sup>r</sup></i> 1964 James Perkins Burling
V. H. Keiser
+ The Diophantine Equation ( <i> x <sub>1</sub> </i> + <i> x <sub>2</sub> </i> + ··· + <i> x <sub>n</sub> </i> ) = <i> x <sup>3</sup> <sub>1</sub> </i> + <i> x <sup>3</sup> <sub>2</sub> </i> + ··· + <i> x <sup>3</sup> <sub>n</sub> </i> 1977 W. R. Utz
+ The Recurrence Relation ( <i>r</i> + 1) <i>f</i> <sub>r+1</sub> = <i>xf</i> <sub>r</sub> + ( <i>K</i> - <i>r</i> + 1) <i>x</i> <sup>2</sup> f <sub>r-1</sub> 1979 F. P. Sayer
+ PDF Chat The approximation solution of<i>y</i><sup>′</sup>=<i>F</i>(<i>x, y</i>) 1968 R. G. Huffstutler
F. Max Stein
+ On the Rational Solutions of <i>x<sup>y</sup></i> = <i>y<sup>x</sup></i> 1990 Marta Sved
+ On the Equation <i>σ</i> ( <i>m</i> ) <i>σ</i> ( <i>n</i> ) = ( <i>m</i> + <i>n</i> ) <sup>2</sup> 1981 Masao Kishore
+ PDF Chat The diophantine equation<i>Y</i>(<i>Y</i>+ 1)(<i>Y</i>+ 2)(<i>Y</i>+ 3) = 2<i>X</i>(<i>X</i>+ 1)(<i>X</i>+ 2)(<i>X</i>+ 3) 1971 John Cohn
+ A Geometric Interpretation of the Solutions of <i>y</i>″ = <i>c</i><sup>2</sup><i>y</i> 1966 Douglas Lind
+ 11. The quadratic equation: <i>ax</i><sup>2</sup> + <i>bx</i> + <i>c</i> = 0 1958 A. G. Sillitto
+ PDF Chat The Diophantine equation<i>x</i><sup>2</sup>= 4<i>q</i><sup><i>n</i></sup>−4<i>q</i>+1 1989 Christopher Skinner
+ 83.27 Integer solutions of <i>a</i><sup>-2</sup> + <i>b</i><sup>-2</sup> = <i>d</i><sup>-2</sup> 1999 Roger Voles
+ ON THE EQUATION Δ<i>u</i>+<i>k</i>(<i>x</i>)<i>e</i><sup><i>u</i></sup>= 0 1978 O A Oleĭnik
+ On the Equation (<i>x</i><sup> <i>m</i> </sup> – 1)/(<i>x</i> – 1) = <i>y</i><sup> <i>q</i> </sup> with <i>x</i> Power 1997 Noriko Hirata-Kohno
T. N. Shorey
+ 97.41 The equation <i>py</i><sup>2</sup> = <i>x</i><sup>4</sup> + <i>x</i> 2013 Stan Dolan

Works Cited by This (0)

Action Title Year Authors